The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.18632/oncotarget.19438
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and stem markers association to PIM1/PIM2 kinase-induced tumors in breast and uterus

Abstract: The PIM family of Ser/Thr kinase proteins has been implicated in tumorigenesis at different levels. PIM proteins are overexpressed in several tumor types and have been associated with chemoresistance. However, their role in hormone-dependent female tissues has not been explored, especially in the uterus, breast and ovary. We generated conditional transgenic mice with confined expression of human PIM1 or PIM2 genes in these tissues. We characterized the tumoral response to these genetic alterations corroboratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 52 publications
(62 reference statements)
0
20
0
Order By: Relevance
“…The panel that we utilized for screening included inhibitors of PKs, 10 of which possessed focused selectivity profiles, while staurosporine was selected as a widely used apoptosis inducer (see Table 1 and supplementary Figure S3). Among PKs targeted by the selective inhibitors were enzymes for which upregulation in endometriotic cells has been reported: MAPKs (Ngô et al, 2010;Yotova et al, 2011), AKT/PKB (Cinar et al, 2009;Shoji et al, 2009), PIM1 (Hu et al, 2006;Jiménez-García et al, 2017), and CK2 (Feng et al, 2012;Llobet et al, 2008). In our study, inhibitors of MAPK (sorafenib), AKT/PKB (GSK690693) and CK2 (ARC-775) were more effective in euESCs than ecESCs, whereas PIM inhibitor (SGI-1776) showed cell type-independent effect: in patients where euESCs were affected, ecESCs were also affected (see supplementary Figure S1B and C).…”
Section: Discussionmentioning
confidence: 99%
“…The panel that we utilized for screening included inhibitors of PKs, 10 of which possessed focused selectivity profiles, while staurosporine was selected as a widely used apoptosis inducer (see Table 1 and supplementary Figure S3). Among PKs targeted by the selective inhibitors were enzymes for which upregulation in endometriotic cells has been reported: MAPKs (Ngô et al, 2010;Yotova et al, 2011), AKT/PKB (Cinar et al, 2009;Shoji et al, 2009), PIM1 (Hu et al, 2006;Jiménez-García et al, 2017), and CK2 (Feng et al, 2012;Llobet et al, 2008). In our study, inhibitors of MAPK (sorafenib), AKT/PKB (GSK690693) and CK2 (ARC-775) were more effective in euESCs than ecESCs, whereas PIM inhibitor (SGI-1776) showed cell type-independent effect: in patients where euESCs were affected, ecESCs were also affected (see supplementary Figure S1B and C).…”
Section: Discussionmentioning
confidence: 99%
“…In recent reports, PIM1 kinase played an important role in regulating triple-negative breast cancer (Braso-Maristany et al, 2016;Horiuchi et al, 2016) and PIM2-specific siRNA treatment was as effective as PIM1-specific siRNA treatment in inhibiting breast cell proliferation, which was more effective in inducing cell death (Horiuchi et al, 2016). Moreover, PIM2 overexpression in mice could promote breast cancer tumorigenesis (Jimenez-Garcia et al, 2017). But the mechanisms of PIM2 by which regulates breast cancer cell proliferation are still unclear, Our data showed that PIM2 was crucial in the regulation of TTP-reduced proliferation and migration in breast cancer cells, consistent with previous studies (Horiuchi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…PIM2 also functions independently of its kinase activity as a co-factor that augments the transcriptional activity of HIF-1a (Yu et al, 2014b). Breast cancer is the most common cancer in women and the second leading cause of cancer death, and it is reported that PIM2-expressing transgenic mice induce breast hyperplasia and tumors (Jimenez-Garcia et al, 2017). However, the mechanisms by which PIM2 regulates breast cancer remain uncharacterized.…”
Section: Introductionmentioning
confidence: 99%
“…upregulated and to be associated with poor survival rates (17). In tumor entities other than liver cancer, PIM2 has been described to directly interact with and phosphorylate cell cycle regulators, p21 WAF1/CIP1 (18) and p27 KIP1 (19), as well as the pro-apoptotic protein, BAD (20), thus facilitating cell survival by maintaining mitochondrial potential (21,22).…”
Section: Inhibition Of Pim2 In Liver Cancer Decreases Tumor Cell Prolmentioning
confidence: 99%